Solar weather station using LoRaWAN, TTN and Azure - Janusz DOROZYNSKI; Jan Marcin ADRIANCZYK; Marek TANDECKI (Communications of International Proceedings, 2021)
This paper presents a study to build a prototype of an unmanned weather station operating as a LoRaWAN end device, equipped with a sensor with an autonomous power system using a battery charged by a solar cell and software created using the Arduino IDE. The created prototype was used to test its performance using The Things Network's public LoRaWAN service platform and MS Azure platform and MS SQL database, as well as using an Android mobile application dedicated to the prototype. Issues related to the Internet of Things are discussed.
Keywords: weather station; LoRa; LoRaWAN; Arduino; Android; IoT; MS SQL; MS Azure